Phytoplankton Supplementation Lowers Muscle Damage and Sustains Performance across Repeated Exercise Bouts in Humans and Improves Antioxidant Capacity in a Mechanistic Animal (vol 12, 1990, 2020) - Sharp, Matthew; Şahin, Kazım; Stefan, Matthew; Orhan, Cemal; Gheith, Raad; Reber, Dallen; Wilson, Jacob (Mdpi, 2022)
[Abstract Not Available]